Multimedia interaktif Multimedia Interaktif “Belajar Kosa-Kata Bahasa Arab” Sebagai Media Edukasi Belajar Bahasa Arab Untuk Anak Sd Kelas IV - Kadariah Kadariah; Ahmad Hamim Thohari; Riwinoto Riwinoto (Politeknik Negeri Batam, 2020)
Appropriate and appropriate learning methods in educating children are veryimportant things. With interactive multimedia technology that is widespread,we can use it as a learning media. Interactive multimedia development makesit possible to create an interactive educational media called